THINKING OF ISLAMIC STUDY IN UNIVERSITIES AS INSPIRATION - Muhammad Agus Kurniawan; Yahya (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
Multicultural Approach For Inspiration and not just conceptually give equality rights of learners to get a chance in any field, but it is also important to explain to students how Islam maintains good relationships with followers outside the Islamic tradition of the Prophet Muhammad ever some centuries ago. Islamic Studies multicultural approach should make the normative foundations of this as a basis to formulate how the process of education in Islam should be managed so that it is no stranger than the people that the laws of nature has its own culture. One of the homework (PR) which is done urgently to review the processes related to learning Islamic studies at universities starting from the historical Christian Apostle Muhammad and the prophets (Moses, Jesus) who brings other major religions, such as Jews and Christians